APPLICATION OF V-ARMA MODEL IN BRIDGE SYSTEM IDENTIFICATION THROUGH AMBIENT TESTING FOR MODAL PARAMETER ESTIMATION - Halim, Handi
Modal parameters can be utilized to monitor the condition of a structure as it reflects the deviation of current condition to the initial condition of a structure. The estimation of these modal parameters is generally done using FFT based algorithms, for example the notorious spectral density peak-picking method. The shortcoming of using this frequency domain modal analysis is the inability to obtain the mode shape, damping ratio and distinguishing between physical and non-physical mode. Therefore, time domain method for obtaining modal parameter estimates is applied. This article presents the results of modal parameters estimation of two bridges in West Java which are Cisangkuy Bridge and Pasupati Bridge in operational condition. The first is a simply supported steel girder bridge and the latter is a continuous span pre-tensioned bridge. The measurement of bridge response to unmeasured and uncontrolled loading was done using tri-axial accelerometer EZDYN. The modal parameters, such as natural frequencies, damping ratios, and vibration mode shapes are obtained by means of operating modal analysis (OMA) in time domain using the measured acceleration and analyzed using Vector Autoregressive Moving Average (V-ARMA). The finite element method based on limited information gained through field survey is also applied as a comparison to the OMA result. The OMA and finite element model shows that both give satisfactory results that confirm each other to some extent, for both natural frequencies and vibration modes of several identified modes of vibration.